IMPLEMENTATION OF HEALTH PROMOTION STRATEGIES IN THE INTEGRATED SERVICE POST PARK PROGRAMS AT THE PUBLIC HEALTH CENTER PESANTREN I KEDIRY CITY - Kurniawan Edi Priyanto; Byba Suhita; Siti Farida (Master of Public Health Program Institut Ilmu Kesehatan STRADA Indonesia, 2017)
Health together with education and economy are the three pillars that greatly affect the quality of human resources. One form of community empowerment efforts in the field of health is to develop Integrated Service Post. Integrated Service Post Park is integrated service post development which is given additional services of Early Childhood Educational Programs and the development of family toodler coaching. To optimize the function of Integrated Service Post Park, it is neccesary to have a special fasicilitator and focus on monitoring, assisting cadres to evaluate and develop Integrated Service Post Park. The purpose of this study is to know the implementation of health promotion strategy in Integrated Service Post Park Program at The Public Healt Center Pesantren I Kediri City.Informants from this study consisted of 4 officers Integrated Service Post Park Facilitator.Data is collected by in-depth interviews. Data is analyzed according to Colaizzi’s stage data analysis. The findings of this study include : Empowerment activities, Social Support activities, Advocacy activities and Partnerships activities. In the implementation of empowerment activities found the training of facilitation officer and cadres are uneven and absence of special means for promotional activities of the Integrated Service Post Park Program. In the implementation of the activity of developing the social support found the existence of problem because of the absence of Early Childhood Education Programs cadres and insufficient means of Educational Game Tools. In the implementation of advocacy activities conducted policy proposals on the establisment of services of early child development cadres and addition of cadres and the addition means of educational game tools.In the implementation of partnership activities have been created a good coordination between the facilitation officers with the stakeholders but there are problems in the mechanism of distributing incentives for facilitation officers and cadres. Recommendations of this study is aimed to facilitation officer of Integrated Service Post Park in helping them to use appropriate health promotion strategies in implementing the Integrated Service Post Park Program activities.